Frontex 3.0 — rewolucyjny czy rewelacyjny — legislacyjno-policyjny paradygmat bezpieczeństwa granic Unii Europejskiej. Paneuropejska interpretacja i implementacja Intelligence-Led Policing - Szostak, Maciej; Zarychta-Romanowska, Kamila (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article contains an analysis of the origins and development of new regulations concerning the European Border and Coast Guard of 2016 and 2018 in order to better understand its tasks and development in the light of the European policy objectives and European law. The authors pay particular attention to the state of ontological uncertainty and lack of security manifested by the residents and states of the European Union. Thus they consider the challenges to the Union’s internal and external security. They analyse new initiatives, both legal and political, the aim of which is to limit the threats associated with uncontrolled irregular migrations, organised crime and terrorism. Examining the EU’s new proposal concerning the European Border and Coast Guard, the authors point to its main objects, innovative nature of the proposed solutions as well as a substantial policy change that can be seen in the new proposal. When analysing the proposal and its amendments from a criminological perspective, the authors indicate a new interpretation of the concept of intelligence-led policing as well as its implementation with regard to the EU’s border and security policies, both in their internal and external aspects. When examining the most important premises of the organisational, institutional and operational mandate of the EBCG, the authors not only examine the establishment of the EU’s new border police, but also confirm the need to define a strategy for the operation of the Service, especially with regard to its operational activities and intelligence, in order for the Service to effectively and fully implement its mandate, at the same time making a major contribution to fighting threats to a broadly defined security of the EU terrorism, uncontrolled migrations, organised crime. What is essential to this is the introduction of a sustainable — respectful of cultural differences but also effective — way to create policing policies as well as use of new technologies to monitor borders, in line with the adopted intelligence policy. In addition, further bi- and multilateral cooperation with relevant bodies and services of third countries should be maintained and developed, especially taking into account the existing good cooperation practices. In the article the authors analyse the regulatory framework of the new regulation specifying the role and threats of the new Service with regard to personnel and insufficient financing, and point to other difficulties associated with the insufficient implementation of the solidarity clause so far. They also point to the urgent need to formulate a methodology, strategy and relevant training enabling border guards to use the so-called cultural profiling taking into account the migrants’ cultural and ideological differences as part of their statutory activities, and at the same time ensuring the highest standard of fundamental right protection.
Keywords: Frontex; migracja; polityka zagraniczna; prawo graniczne; działania policyjne oparte na danych wywiadowczych; policja; kontrola graniczna; Europejska Straż Graniczna i Przybrzeżna; bezpieczeństwo; ochrona granicy; Schengen; polityka karna UE; zasada solidarności